Angels Watching Over Me : An Extraordinary Investigation into Experiences of Afterlife Communication - Newcomb, Jacky (Australia Hay House, 2007)
Offers a glimpse into the magical stories of communication between our world and the next. This work illustrates the power of real-life spontaneous afterlife experiences and how they show that life goes on after we leave the physical realm
Keywords: Spiritualism -- Future life